Dilated common bile duct and deranged liver function tests associated with ketamine use in two HIV-positive MSM. (August 2013) - Zhou, Judith; Shaw, Simon G; Gilleece, Yvonne
We report here the first two cases of hepatobiliary pathology in HIV-positive men following recreational use of ketamine: >1 g/day over a 12-month period while on ritonavir-based antiretroviral therapy. Presentation in each case was acute with nausea, vomiting and epigastric pain. Alanine aminotransferase was raised at 3.2× and 10.1 × upper limit of normal and alkaline phosphatase was raised at 1.7× and 2.5 × ULN for cases 1 and 2, respectively. Magnetic resonance cholangiopancreatography showed dilatation of the common bile duct; case 1, 18 mm and case 2, 14 mm with no ductal obstruction on endoscopic retrograde cholangiopancreatography. The symptoms resolved, common bile duct dilatation and liver function improved on discontinuation of ketamine use. Time to development of symptoms is shorter than reported in HIV-negative cases (12 months vs. 4 years) which may be explained by an interaction between ketamine and ritonavir.